The Effectiveness of CoRT Program for Teaching Thinking in Developing the Intellectual and Imaginative Side in Creative Writing among Pupils of the Second Cycle of Basic Education Stage. - Taha Hussien (International Journal of Advanced Humanities Research)
CoRT program is one of the most famous programs for teaching thinking. the current research is trying to determine the effectiveness of training on the thinking tools of the parts: the first " Breadth ", the fourth "Creativity", and the sixth " Action " from the CoRT program after integrating them into the Arabic language curriculum for the second year of preparatory school, the second semester , in the creative writing skills of the experimental study sample. The current research used the experimental method with two groups: experimental and control, with a pre and post-tests for each of the two groups. The research was conducted on (54) male and female students of the second year of middle school, divided into two experimental and control groups, each group consisting of (14 males and 13 females). The training program consists of thirty sessions. The results indicated that there were statistically significant differences between the experimental and control groups in the post-test of the intellectual and imaginative aspects in creative writing after isolating the effect of the pre-test.